RANCANG BANGUN PERKAKAS SEDERHANA BERUPA KOMPRESOR DAN GERINDA UNTUK PENGRAJIN PANDAI BESI - Jasron, J. U.; Sanusi, A.; Bunganaen, W. (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana Mengabdi, 2022)
The blacksmith business groups in Kota Kupang and Kabupaten Kupang are still classified as small businesses and community groups that also influence local revenue (PAD). To increase the quality and quantity of production products, these business groups must acquire knowledge and equipment based on appropriate technology. According to the survey results and interviews with the two partners, data and the fact that so far, the two partners have only used bicycle wheels as a tool to produce the wind needed during the heating process in the combustion kitchen. In this activity, the activity implementer will make an appropriate tool To produce wind. It is by utilizing a compressor that can accommodate the wind in the reservoir to ease the work. Apart from that, grinding tools were also made to help workers smooth their products, which they had to do in workshops because of the absence of grinding tools. The method used in the implementation of this activity is the method of designing tools with a sequence of implementation starting from the preparation of work drawings, tools, and materials, work by work drawings, assembly, testing, and adjustment at partner workplaces to the operation of tools and instructions regarding tool maintenance for both. It is hoped that partners will be directly involved in the working process because both partners have the ability from the side of the experience that has been in the field for a long time.   Keywords: Compressors, Grinders, Blacksmiths, Furnace, Products.